2016
DOI: 10.4238/gmr.15028320
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the IL-10 promoter polymorphisms and pediatric asthma susceptibility

Abstract: ABSTRACT. The results of previous epidemiological studies exploring the relationship between interleukin-10 (IL-10) promoter polymorphisms and susceptibility to pediatric asthma are not consistent. Therefore, we have performed a systematic review and meta-analysis to provide a more convincing conclusion. Odds ratios (OR) with their 95% confidence intervals (CIs) were used to evaluate the strength of association between the IL-10 promoter polymorphisms and susceptibility to pediatric asthma. Publication bias wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
2
13
0
2
Order By: Relevance
“…This result corroborates those obtained by Silva et al [2016] in a systematic literature review on the etiology of MIH, which reported that early childhood disease represents an etiological factor of MIH, in particular fever, asthma, and pneumonia. It is interesting to mention that interleukin family genes have been associated with a greater susceptibility to the development of respiratory diseases [Du et al, 2016;Huang et al, 2016;Hyun et al, 2013;Korytina et al, 2016]. Although the other environment covariates analyzed here were not significantly related with the MIH in the families studied, this does not mean that those environment covariates have no influence in the MIH development.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…This result corroborates those obtained by Silva et al [2016] in a systematic literature review on the etiology of MIH, which reported that early childhood disease represents an etiological factor of MIH, in particular fever, asthma, and pneumonia. It is interesting to mention that interleukin family genes have been associated with a greater susceptibility to the development of respiratory diseases [Du et al, 2016;Huang et al, 2016;Hyun et al, 2013;Korytina et al, 2016]. Although the other environment covariates analyzed here were not significantly related with the MIH in the families studied, this does not mean that those environment covariates have no influence in the MIH development.…”
Section: Discussionmentioning
confidence: 44%
“…This result supports our hypothesis that polymorphisms in immune response genes reported as associated with inflammatory diseases considered MIH etiologic factors, such as asthma, ear infections, respiratory tract infections, and allergies [Alaluusua, 2010;Crombie et al, 2009;Silva et al, 2016], may also impact the development of MIH. We highlight the first evidence demonstrated here of the interaction between the rs6654939 SNP in the AMELX gene with the polymorphisms in the IL10 and IL17A, that were reported as risk factors for the development of asthma [Du et al, 2016;Huang et al, 2016] and otitis media [Emonts et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…67 Moreover, the same variant was associated with pediatric asthma. 68 In an endemic area for S mansoni, alleles at the 3 promoter SNPs were associated with high tIgE levels in the same direction as in atopic subjects but not with egg counts. IL10 promoter polymorphisms appear to influence nonspecific tIgE levels but not schistosomiasisspecific immunity.…”
Section: Variants That Affect the T H 2 Immune Responsementioning
confidence: 85%
“…Two meta‐analyses have been published on the associations between IL‐10 rs1800896 (‐1082A/G), rs1800871 (‐819C/T) or 1800872 (‐592C/A) polymorphisms and asthma . The meta‐analysis published in 2014 comprised 4716 adults and children with asthma and 5093 controls .…”
Section: Discussionmentioning
confidence: 99%
“…The result concerning the IL‐10 rs1800896 polymorphism was in agreement with the observations in the present study. The meta‐analysis published in 2016 comprised 2494 children with asthma and 2160 controls and included nine of the 11 paediatric studies in the 2014 meta‐analysis . The conclusion was that there were no significant associations between the IL‐10 rs1800896, rs1800871 or rs1800872 polymorphisms and susceptibility to paediatric asthma .…”
Section: Discussionmentioning
confidence: 99%